2017
DOI: 10.1111/aas.13043
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between McGrath MAC videolaryngoscopy and Macintosh laryngoscopy in children

Abstract: McGrath VL provides better laryngeal views and lower IDS but similar intubation times and success rates compared with the Macintosh laryngoscope in children with normal airway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 15 publications
4
30
0
3
Order By: Relevance
“…In other manikin and clinical studies, a video laryngoscope provided a good laryngeal view or high POGO score. 13,14 In the present study, the IS had a mean POGO score of 75% AE 23%, similar to other videolaryngoscopes.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In other manikin and clinical studies, a video laryngoscope provided a good laryngeal view or high POGO score. 13,14 In the present study, the IS had a mean POGO score of 75% AE 23%, similar to other videolaryngoscopes.…”
Section: Discussionsupporting
confidence: 83%
“…Therefore, an observer effect might have occurred during the performance of intubation and affected the hemodynamic responses. 13 Third, because we only compared the IS and DL, further studies comparing the IS with other lighted stylets or videolaryngoscopes might produce different results.…”
Section: Discussionmentioning
confidence: 99%
“…Einige SR deuten auf ein erhöhtes Risiko einer verlängerten Intubationszeit und einer erfolglosen Intubation mit Videolaryngoskopie hin [ 192 194 ]. Neuere RCT- und Beobachtungsstudien deuten auf einen Vorteil hin, aber die Evidenzen bleiben widersprüchlich [ 195 202 ]. Wichtig ist, dass ein solcher Vorteil stark davon abhängt, wer die Intubation durchführt, welche Technik und welches Gerät für welche Indikation verwendet werden.…”
Section: Evidenzen Für Die Leitlinienunclassified
“…Relevant paediatric intubation study reported an intubation time of a mean 27.5 seconds with a standard deviation of 8.9 seconds. 15 The minimum number of patients for each group resulted in 62, and considering the 10% dropout rate, we planned to enroll 68 patients for each group (α = 0.05, β = 0.2).…”
Section: Sample Size Calculation and Statistical Analysismentioning
confidence: 99%